Factors associated with neurocognitive disorders in people living with HIV aged ≥ 50 years old in Brazil: a cross-sectional study - Julio Cesar Matias do Nascimento; Guilherme Welter Wendt; Joana Perotta Titon; Geraldo Emílio Vicentini; Lia Beatriz Henke de Azevedo; Lirane Elize Defante Ferreto (ABCS Health Sciences)
Introduction: There is a high prevalence of HIV-associated neurocognitive disorders (HAND), especially in people living with HIV (PLWH) who are ≥50 years old. Objective: The objective of this study was to identify the factors associated with HAND in PLWH who are ≥50 years old. Methods: This is a cross-sectional study involving 48 patients (Mean=59.6 years). We collected sociodemographic, clinical, and anthropometric data, and the instrumental activities of daily living (IADL) and International HIV Dementia Scale (IHDS) were administered for neurocognitive evaluation. Results: A total of 75% of individuals had HANDs, including 88.89% with asymptomatic disorders and 11.11% with mild/moderate disorders. IHDS scores were positively correlated with educational level, nutritional status, and viral load (VL) at the time of diagnosis, while negatively correlated with the number of diseases, number of medications, and blood glucose levels. Conclusion: To the best of our knowledge, this is one of few studies conducted exclusively with elderly PLWH that investigated the factors associated with HAND in an inland city from a developing country, showing that the main predictors of HANDs were education, VL at diagnosis, and blood glucose. Hence, results could support future studies and interventions among PLWH elsewhere, where resources are limited and HIV assistance may be more precarious and difficult.